ADVANCED FOREIGN PRACTICES IN TEACHING EDUCATION LAW - A. Yakubov (European Science Publishing, 2024)
This article analyzes advanced foreign practices in teaching education law. Using examples from leading educational systems worldwide, such as the USA, Canada, the United Kingdom, and European countries, the article examines innovative approaches, new pedagogical methods, and modern technologies applied in teaching education law. Additionally, the opportunities for developing this subject in Uzbekistan and the possibilities of applying foreign experiences in practice are discussed.
Keywords: Pedagogical Methods, Innovative Teaching Approaches, Case Study Method, Legal Education, Higher Education, Uzbekistan.